Enhancing EFL Learners’ Reading Vocabulary Acquisition through Task-Based Instruction - Guntur Rahmat Ramadhan; Ali Saukah; Sri Andreani (Universitas Negeri Malang, 2021)
Abstract: This study is intended to enhance students’ reading vocabulary through task-based instruction. It was also devised not only to answer how the strategy can enhance students’ reading vocabulary but also to get data about students’ vocabulary retention two weeks after the implementation and students’ responses towards the strategy. The participantS of this study were 30 ninth graders in SMPN 11 Malang in the second semester of 2019/2020 academic year. Classroom Action Research (CAR) was used as the research design. Vocabulary test, questionnaire, observation sheet, and interview session were the instruments of this study. There were three vocabulary tests, namely vocabulary test one, vocabulary test two, and delayed test. The result showed that there was an improvement in students' scores. 90% of students achieved at least 25 improvement points for the vocabulary test two, 61% of students passed the delayed vocabulary test, and 97.5% of students responded positively toward the strategy. TBI could enhance vocabulary acquisition from the context and task’s characteristics. The context of the text helped students to give a clue about some forgotten vocabularies, so they felt less burdened to remember the vocabulary in the whole text because they generally understand the context of the text. Keywords: task-based instruction, reading vocabulary, vocabulary retention Abstrak: Penelitian ini bertujuan untuk meningkatkan kosakata membaca siswa melalui instruksi berbasis tugas. Penelitian ini juga dirancang tidak hanya untuk menjawab bagaimana strategi yang diterapkan dapat meningkatkan kosakata membaca siswa tetapi juga untuk mendapatkan data tentang retensi kosakata siswa dua minggu setelah penerapan dan tanggapan siswa terhadap strategi yang diberikan. Partisipan penelitian ini adalah 30 siswa kelas 9B di SMPN 11 Malang semester genap tahun ajaran 2019/2020. Penelitian Tindakan Kelas (PTK) digunakan sebagai desain penelitian. Tes kosakata, angket, lembar observasi, dan sesi wawancara menjadi instrumen dalam penelitian ini. Ada tiga tes kosakata yang diberikan, yaitu tes kosakata satu, tes kosakata dua, dan tes tertunda. Hasil penelitian menunjukkan bahwa ada peningkatan pada nilai siswa: 90% dari keseluruhan siswa mencapai setidaknya 25 peningkatan poin untuk tes kosakata dua, 61% dari keseluruhan siswa mampu melalui tes kosakata tertunda, dan 97.5% dari keseluruhan siswa menanggapi strategi secara positif. TBI dapat meningkatkan penguasaan kosakata dari suatu konteks dan karakteristik tugas. Konteks dari suatu teks membantu siswa mendapatkan petunjuk tentang beberapa kosakata yang telah terlupakan, sehingga mereka merasa tidak terlalu terbebani untuk mengingat kembali kosakata keseluruhan teks karena mereka pada umumnya memahami konteks teks tersebut. Kata kunci: instruksi berbasis tugas, kosakata bacaan, retensi kosakata